The Sacred Mountain of Colombia's Kogi Indians - Reichel-Dolmatoff, G. (Iconography of Religions, 1990)
The Kogi Indians of the Sierra Nevada, an isolated mountain massif of northern Colombia, have preserved much of their cultural heritage, notwithstanding the onslaught of outside influences. To the casual observer their austere and withdrawn way of life presents a picture of abject poverty but long-term ethnological study reveals dimensions of inner depth which are evidence of a very rich and cherished tradition going back to pre-Conquest times. Kogi cosmogony and cosmology, their religious philosophy, and their interpretation of nature, as described by men of priestly training, bear witness to a creative imagination of great power. This study tells us of their macrocosm and microcosm; the structure of the universe and the spinning of cotton thread; time-space concepts and the symbolism of a small gourd vessel; biological cycles and temple architecture, and all this within the compass of a sacred mountain which to the Kogi is the centre of the universe. The ethnological importance of this essay is equalled by its value to the Humanities, and opens a new dimension of Amerindian studies.